Psychological morbidity, sexual satisfaction, coping and quality of life in women with urinary incontinence in rehabilitation treatment - Pereira, M. Graça (2018)
This chapter focuses on the relationships between psychological morbidity, sexual satisfaction, coping, and quality of life in women with urinary incontinence in rehabilitation treatment, taking into consideration the women's perception of ﻿the severity of the urine loss and the type of urinary incontinence. Women that consider their incontinence symptoms as moderate reported better quality of life, and those with mild symptoms reported greater sexual satisfaction. Women with severe symptoms relied on religion and used more self-blame coping, expression of feelings, denial, and self-distraction strategies. Women with stress urinary incontinence used active coping while women with urge urinary incontinence used ﻿behavioral disinvestment, as coping strategies. Given the impact of urinary incontinence in women’s lives, it would be important to develop health promotion strategies in order to help women cope and, as a result, improve their quality of life and the associated psychological symptoms.